Determinants of MSME’s Financial Management - Tantri Nandita Aulia; Indri Kartika (Athallah Publishing Globalindo, 2026)
This study aims to analyze the influence of financial literacy, financial inclusion, digital transformation, and accounting information systems on the financial management among culinary MSMEs in Semarang City. This study employed a quantitative approach using primary data collected through questionnaires distributed to 99 culinary MSME owners in Semarang City using a purposive sampling technique. The data analysis method used was multiple linear regression analysis with the assistance of IBM SPSS Statistics.The results of the study indicate that financial literacy has a positive and significant effect on the MSME’s financial management. Financial inclusion has a positive and significant effect on the MSME’s financial management. Digital transformation also has a positive and significant effect on the MSME’s financial management. Meanwhile, the accounting information system has a negative and insignificant effect on the MSME’s financial management. Future researchers can improve the research model by adding other variables such as: digital payment transformation variables, financial education, or digital financial capabilities. Interview methods can be an alternative to obtain more valid data. MSME’s management are expected to improve their financial management skills and utilize digital technology optimally to make business management more effective and efficient. The government and related institutions are expected to increase training, mentoring, and support for access to financing for MSMEs to improve business efficiency and competitiveness.